A lake-level chronology based on feldspar luminescence dating of beach ridges at Tangra Yum Co (Southern Tibet). Issue 3 (May 2015) - Rades, Eike F.; Tsukamoto, Sumiko; Frechen, Manfred; Xu, Qiang; Ding, Lin
Abstract : Many lakes on the Tibetan Plateau exhibit strandplains with a series of beach ridges extending high above the current lake levels. These beach ridges mark former lake highstands and therefore dating their formation allows the reconstruction of lake-level histories and environmental changes. In this study, we establish a lake-level chronology of Tangra Yum Co (fifth largest lake on the Tibetan Plateau) based on luminescence dating of feldspar from 17 beach-ridge samples. The samples were collected from two strandplains southeast and north of the lake and range in elevation from the current shore to 140 m above the present lake. Using a modified post-infrared IRSL protocol at 170°C we successfully minimised the anomalous fading in the feldspar IRSL signal, and obtained reliable dating results. The luminescence ages indicate three different stages of lake-level decline during the Holocene: (1) a phase of rapid decline (~ 50 m) from ~ 6.4 to ~ 4.5 ka, (2) a period of slow decline between ~ 4.5 and ~ 2.0 ka (~ 20 m), and (3) a fast decline by 70 m between ~ 2 ka and today. Our findings suggest a link between a decrease in monsoonal activity and lake-level decline since the early Holocene.